The Effect of Video Use in the Problem Based Learning Model on Students Mathemathical Representation Abilities - Sephia Virgiani Effendi; Nurhanurawati; Agung Putra Wijaya (Universitas Teknokrat Indonesia, 2026)
This study investigated the effect of video-assisted Problem-Based Learning (PBL) on students’ mathematical representation abilities. The study population consisted of all Grade VIII students of SMP Negeri 14 Bandar Lampung in the 2025/2026 academic year, encompassing eleven classes (VIII-A to VIII-K). Using purposive random sampling, 30 students from class VIII-I and 32 students from class VIII-J were selected as the research sample. The study adopted a pretest–posttest control group design, in which class VIII-J served as the experimental group and received video-assisted PBL, while class VIII-I served as the control group and received PBL without video assistance. Quantitative data were obtained through a mathematical representation ability test. The results of the t-test revealed that the increase in mathematical representation ability among students in the experimental group was significantly higher than that of students in the control group. Therefore, video-assisted PBL has a significant positive effect on students’ mathematical representation abilities.